If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(x+4)=5(x-6)+36
We move all terms to the left:
3(x+4)-(5(x-6)+36)=0
We multiply parentheses
3x-(5(x-6)+36)+12=0
We calculate terms in parentheses: -(5(x-6)+36), so:We get rid of parentheses
5(x-6)+36
We multiply parentheses
5x-30+36
We add all the numbers together, and all the variables
5x+6
Back to the equation:
-(5x+6)
3x-5x-6+12=0
We add all the numbers together, and all the variables
-2x+6=0
We move all terms containing x to the left, all other terms to the right
-2x=-6
x=-6/-2
x=+3
| 5(k-4)+k=-8 | | x+39=90+147=360 | | 120+22x+4=15+5 | | -10-1-9w=7-6w | | r/14=3 | | 532=4z | | 4x+25=39 | | 5y/100=y-11970 | | 5(c-1)+2=3(c=+1)-2 | | 4x+10=39 | | (1/3^x)=81^-1 | | 10y–2y=64* | | 165x=-1580 | | 18x+3/4=336 | | 4h-11=45 | | 17=p | | 7x+12+2=44 | | 5(c-1)+2=3(c-1)-2 | | x/3-9=-8 | | 4y-36=2y=42 | | F(4)=-1/2x+2 | | x+20+45=360 | | F(2)=-1/2x+2 | | 4b-1=-5 | | r−2/3=7 | | 40x+(1500-50x)=1350 | | -8.21+5.5s=9.48+8.4s | | 5x-5=5(x+1)+5 | | t−1.5=7.9 | | 4(x−3)−=7x≥6 | | F(0)=-1/2x+2 | | –6n=10−5n |